2009
DOI: 10.1038/nature07720
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of an avian influenza polymerase PAN reveals an endonuclease active site

Abstract: The heterotrimeric influenza virus polymerase, containing the PA, PB1 and PB2 proteins, catalyses viral RNA replication and transcription in the nucleus of infected cells. PB1 holds the polymerase active site and reportedly harbours endonuclease activity, whereas PB2 is responsible for cap binding. The PA amino terminus is understood to be the major functional part of the PA protein and has been implicated in several roles, including endonuclease and protease activities as well as viral RNA/complementary RNA p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
540
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 452 publications
(561 citation statements)
references
References 34 publications
17
540
0
4
Order By: Relevance
“…PB2 is a cap-binding peptide mediating association with the caps of pre-mRNAs. [45][46][47] Recent data indicates that the endonuclease activity for pre-mRNA scission and generation of the capped oligomer resides with PA. 48,49 PB1 has intrinsic polymerase activity and is responsible for both mRNA elongation and correct association with the viral RNA template. 50 In contrast to influenza virus, bunya-and arenavirus replication is exclusively cytoplasmic and caps are thus derived from mRNA rather than pre-mRNA.…”
Section: Association Of N With the Mrna Degradation Apparatus During mentioning
confidence: 99%
“…PB2 is a cap-binding peptide mediating association with the caps of pre-mRNAs. [45][46][47] Recent data indicates that the endonuclease activity for pre-mRNA scission and generation of the capped oligomer resides with PA. 48,49 PB1 has intrinsic polymerase activity and is responsible for both mRNA elongation and correct association with the viral RNA template. 50 In contrast to influenza virus, bunya-and arenavirus replication is exclusively cytoplasmic and caps are thus derived from mRNA rather than pre-mRNA.…”
Section: Association Of N With the Mrna Degradation Apparatus During mentioning
confidence: 99%
“…95 Although it has been reported that alternative binary complexes of the polymerase subunits might be responsible for transcription or replication, 120,121 a number of other reports indicate that the polymerase heterotrimer is the functional unit in both processes. 8,48,49,63,66,122 Altogether, the genetic approaches indicated above enabled the proposal of a new model for influenza RNA replication, which is depicted in the diagram presented in Figure 5. Activation of vRNA synthesis would result from the interaction of a soluble polymerase complex (Non-resident polymerase-NRP1-) with the cRNP (Fig.…”
Section: Virus Genome Amplificationmentioning
confidence: 99%
“…2). In addition to the subunit interfaces mentioned above, the atomic structures of domains of the PA and PB2 subunits have been determined 47,55,56,[63][64][65][66][67] but no information on the structure of the polymerase active site in the PB1 subunit is yet available. The data reported allowed the identification of the polymerase cap-binding site in PB2 and established that the endonuclease responsible for cap-snatching resides at the N-terminal region of PA, in agreement with previous genetic contacts detected in the cryo-EM structure of the mini-RNP.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
See 1 more Smart Citation
“…ISAV, as with the infl uenza viruses, has an U residue at the 3'-end of the vRNA but this U residue is lost in the cap-stealing process, and the penultimate C residue at the 3'-end of the vRNA then becomes the fi rst nucleotide transcribed by the ISAV polymerase, which is similar to how infl uenza virus vRNA is transcribed [26,27]. The capstealing endonuclease activity of infl uenza virus lies in the PA subunit of the polymerase [28,29], and this subunit could thus be an attractive target for anti-infl uenza drugs. The capstealing endonuclease activity of ISAV has not been mapped in detail to any particular polymerase subunit.…”
Section: Replicationmentioning
confidence: 98%